Tratamento de efluentes têxteis por processo eletrolítico com corrente direta pulsada em escala laboratorial e piloto visando o reuso no processo produtivo - Ribeiro, Jefferson Pereira (2017)
The textile industry is considered as one of the most polluting activities of all industrial processes, due to the high volume and composition variation of its effluents. In this context, the present study evaluated the use of electrocoagulation technology with pulsed direct current in order to treat and reuse water from the post-dyeing of cotton yarns generated in the textile industry. Experiments were carried out using Box-Behnken factorial design using real effluent, in order to determine which factors were most relevant for the removal of the dyes present in the aqueous effluent. The experiments were carried out in an electrocoagulation-flotation (ECF) reactor built in acrylic, operating in batch, with dimensions of 60.0 cm in height and 10.0 cm in diameter, resulting in a total useful volume of 4.710 cm3. The Box-Behnken design proved to be an important tool to evaluate the effect of the main factors (pH, agitation speed and frequency) and their interactions in the process of discoloration of the actual textile effluent. The color removal percentages ranged from 52.76 - 95.24%, with highlight to experiment 16, which obtained the highest percentages of removal in the experimental conditions (pH 7, frequency 1400 Hz, agitation of 800 rpm). This study provided the development of mathematical models that could help predict the process of color removal of the textile effluent, considering the range of levels studied. The results of characterization of the residues of the electrolytic process also registered the high presence of organic matter loading, sodium chloride. The results obtained in the laboratory-scale study indicate that the electrocoagulation / flocculation process has a high potential to be applied on a pilot scale. The use of the electrolytic process with pulsed direct current allowed the reduction of energy costs above 50%, making possible the use of technology in the textile industry. In the study carried out in the pilot treatment unit, a 90% efficiency of color removal of the effluent from the dyeing step was obtained.